ChemInform Abstract: Gold(I)‐Catalyzed Dehydrative Formation of Ethers from Benzylic Alcohols and Phenols. Issue 47 (November 2015) - Veenboer, Richard M. P.; Nolan, Steven P.
Abstract: A cross‐dehydrative reaction of two alcohols proceeds under mild reaction to give unsymmetrical ethers (III) using NHC—gold(I) complex IPR.